The effect of 3D modeling performed using Tinkercad or concrete materials in the context of the flipped classroom on pre-service teachers’ spatial abilities - YILDIRIM, MEHTAP (My University, 2023)
Background: Spatial ability has an important place in science education, which is effective in raising future scientists. Although not in large numbers, studies show that teachers’ spatial abilities somehow affect their teaching practices in the classroom and thus the spatial abilities of their students. Purpose: This study aimed to investigate the effect of 3D modeling activities performed by preservice science teachers in the Biology course using Tinkercad or concrete materials in the context of the Flipped Classroom (FC) model on their spatial ability. Sample: The participants of the study were fifty-seven preservice science teachers studying at a state university in Istanbul, Turkey. Design and methods: The study was designed according to the explanatory sequential design. The Purdue Spatial Visualization Test was utilized to investigate the effect of the implementation on the participants’ spatial abilities. In addition, semi-structured interviews were conducted with twenty-four participants to examine their experiences regarding the implementation. Conclusions: The results of the study show that 3D modeling performed in the context of the FC model, regardless of Tinkercad or concrete materials are used, improves the spatial abilities of preservice teachers, as well as 3D modeling with Tinkercad, is a more effective implementation to develop spatial ability. While the participants’ statements supported the quantitative results, they were toward that the classroom atmosphere they missed during the pandemic process was created by the FC model’s in-class process and there was a significant improvement in their communication skills.
Keywords: Sosyal ve Beşeri Bilimler; Sosyoloji; Eğitim; Social Sciences and Humanities; Sociology; Education; Sosyal Bilimler (SOC); Sosyal Bilimler Genel; EĞİTİM VE EĞİTİM ARAŞTIRMASI; Social Sciences (SOC); SOCIAL SCIENCES, GENERAL; EDUCATION & EDUCATIONAL RESEARCH; Sosyal Bilimler ve Beşeri Bilimler; Social Sciences & Humanities; 3D modeling; flipped classroom; pre-service teachers; science education; spatial ability